"Well Duh, That's How You Raise a Kid": Gender-Open Parenting in a (Non)Binary World. Issue 3 (25th July 2022) - Rahilly, Elizabeth
Abstract: While parenting practices that resist traditional gender norms for children are not new, the advent of "gender-open parenting" in recent years poses a new and understudied phenomenon in childhood socialization. Assisted by new "nonbinary" gender possibilities and pronouns, these parents: do not assign a sex/gender to their child, keep their child's anatomy private, and use they/them pronouns until the child can express their own sense of gender. Using interview data from 21 parents and 11 grandparents, this study presents foundational insights on their gender-open practices, including their educating others, birth plans, and gender-neutral language. Discussion and analysis employs Risman's concept of "gender as a social structure" to map these practices onto broader dimensions of our social structure, exposing their potential for significant social change. Parents' efforts reflect the multi-dimensional nature of gender in society, where all levels are engaged to resist cisgender norms and ideologies—including individual, interactional, and institutional. Conclusion addresses implications for educators, clinicians, and policymakers, as well as future research.